2020
DOI: 10.1038/s41598-020-74771-w
|View full text |Cite
|
Sign up to set email alerts
|

Altered amygdala-based functional connectivity in individuals with attenuated psychosis syndrome and first-episode schizophrenia

Abstract: Altered resting-state functional connectivity (FC) of the amygdala (AMY) has been demonstrated to be implicated in schizophrenia (SZ) and attenuated psychosis syndrome (APS). Specifically, no prior work has investigated FC in individuals with APS using subregions of the AMY as seed regions of interest. The present study examined AMY subregion-based FC in individuals with APS and first-episode schizophrenia (FES) and healthy controls (HCs). The resting state FC maps of the three AMY subregions were computed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A fourth trend evident in Figure 2 is that reduced FC in CST circuitry is a common finding across all illness stages, with the reductions being particularly widespread in schizophrenia (134,141,144,166). There is some evidence for increased FC within the ventral circuitry across clinically significant stages of illness (i.e., at-risk, first-episode and established schizophrenia) and while the specific circuit elements affected vary across stages, the amygdala is consistently involved in these increases (167)(168)(169)(170). This evidence of selective FC increases coupled with widespread FC reductions aligns with prior reports that consistent FC increases within specific neural systems, such as between sensorimotor corticothalamic circuits (141,145,171), may occur against a backdrop of globally reduced FC in patients (172).…”
Section: Evidence Of Cst Dysconnectivity In Human Neuroimaging Studiesmentioning
confidence: 90%
“…A fourth trend evident in Figure 2 is that reduced FC in CST circuitry is a common finding across all illness stages, with the reductions being particularly widespread in schizophrenia (134,141,144,166). There is some evidence for increased FC within the ventral circuitry across clinically significant stages of illness (i.e., at-risk, first-episode and established schizophrenia) and while the specific circuit elements affected vary across stages, the amygdala is consistently involved in these increases (167)(168)(169)(170). This evidence of selective FC increases coupled with widespread FC reductions aligns with prior reports that consistent FC increases within specific neural systems, such as between sensorimotor corticothalamic circuits (141,145,171), may occur against a backdrop of globally reduced FC in patients (172).…”
Section: Evidence Of Cst Dysconnectivity In Human Neuroimaging Studiesmentioning
confidence: 90%
“…Additionally, we demonstrate the developmental drop in CMA -frontal connectivity is most severe in patients at a higher risk for positive psychotic symptoms. The accelerated decrease in CMA to frontal connectivity has been previously documented in youth with psychosis (50)and in patients with attenuated psychotic symptoms (51). The loss of connection in this circuit could contribute to the prodromal loss of emotional regulation that often precedes psychosis in schizophrenia (97).…”
Section: Discussionmentioning
confidence: 81%
“…In doing so, Jalbrzikowski et al (2019) have identified abnormal development of CMA functional connectivity during early adolescence in patients with psychosis disorders (50). Additionally, another study on adults with schizophrenia has identified abnormal SFA and CMA functional connectivity in adults with psychosis(51). Regarding how amygdala dysfunction and stress interact in psychosis, findings in mice models for schizophrenia points to a direct link between stress behavior caused by BLA hyperactivation, that aggravates a cascade of neurobiological changes that result in psychosis (52, 53).…”
Section: Introductionmentioning
confidence: 99%
“…31 It has been extensively employed in a range of objective assessments of brain functioning, such as in sleep and neuropsychiatric disorders. 20,32 However, the FC pattern in the amygdala subregions of patients with OSA after CPAP treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%